Assessment of environmental degradation on the Mostaganem Plateau Algeria: A critical analysis of soil and water resources - Ouabel, Habib; Taleb, Mohamed Lamine; Hamadi, Amina (Future Science, 2024)
This study underscores the importance of accounting for spatial dimensions and temperatures in evaluating payments and environmental interactions. Exploiting natural spaces can foster sustainable development, especially in vulnerable areas, but urbanization poses significant challenges. The Mostaganem Plateau, spanning 78,100 hectares with diverse landscapes, is highly sensitive to environmental pressures like abrasion. Urbanization, agriculture, industry, deforestation, and heavy port activities threaten its biodiversity. Using the plateau as a diagnostic tool helps identify the main causes of its deterioration. Analyzing agricultural and industrial impacts on soil and water highlights the severity of the situation. These analyses, along with in-depth geographic studies, reveal the complex decomposition processes driven by natural and human factors. Implementing effective political policies and management practices is crucial to counter negative influences and promote sustainable development. Protecting the Mostaganem Plateau's fragile ecosystem requires vigilant efforts from the scientific community and social and economic stakeholders. Addressing environmental and ecological impacts is essential for long-term development. Practical responses are needed to mitigate severe degradation and preserve the plateau's environmental integrity for future generations. The study emphasizes the urgent need for monitoring and intervention to safeguard this vulnerable region, ensuring its sustainability and resilience against ongoing threats. Protecting the Mostaganem Plateau's fragile ecosystem requires vigilant efforts from the scientific community and social and economic stakeholders. Addressing environmental and ecological impacts is crucial for long-term development. Practical responses are needed to mitigate severe degradation and preserve the plateau's environmental integrity for future generations.